Thinking about research paradigms in educational research - Wang, Shiyun; Zhu, Pengju (Advances in Social Sciences Research Journal, 2016)
In this essay, I will consider the question “what is research” and discuss the three important research paradigms. The three important research paradigms are positivistic, interpretive and critical paradigms. First of all, I try to explain the definition of research deeply. Many scholars give us many different definitions of research, these definitions explain the research from different aspects, and they have respective characteristics. At the same time, I will try to make clear what educational research is. Secondly, I focus on the nature and significance of research paradigms and reasons why these are important in thinking about research. Thirdly, I will comment on the characteristics of “good” and “bad” research in terms of my own experience. Finally, I will analyze qualitative approaches and quantitative approaches; my purpose is to explain why so much research in education employs qualitative approaches.